Suicide by pesticide ingestion in Nepal and the impact of pesticide regulation - Leah Utyasheva; Dilli Sharma; Rakesh Ghimire; Ayanthi Karunarathne; Gael Robertson; Michael Eddleston (BMC, 2021)
Abstract Background Nepal recorded 5754 suicides in 2018-19 - a high number for a relatively small country. Over 24% of these suicides were by poisoning, most by ingestion of highly concentrated agricultural pesticides. Nepal has actively regulated pesticides to reduce their health impacts since 2001. We aimed to analyse Nepal's history of pesticide regulation, pesticides responsible for poisonings, and relate them to national suicide rates. Methods Information on pesticide regulation was collected from the Plant Quarantine and Pesticide Management Centre of the Ministry of Agriculture and Livestock Development. National data on suicides from 1980 to 2019 were obtained from the National Statistical Bureau and Nepal Police. Data on the pesticides responsible for self-poisoning and pesticide suicides over time were obtained from a systematic literature review. Results As of June 2020, 171 pesticides were registered for use in Nepal, of which one was extremely hazardous (WHO Class Ia), one other highly hazardous (WHO Class Ib), and 71 moderately hazardous (WHO Class II). Twenty-four pesticides have been banned since 2001, with eight (including five WHO Class I compounds) banned in 2019. Although the suicide rate has increased more than twelve-fold since 1980, particularly for hanging (15-fold increase from 1980 to 2018), fatal pesticide self-poisoning has increased by 13-fold. Methyl-parathion is reported to be the key pesticide responsible for pesticide self-poisoning in Nepal, despite being banned in 2006. Conclusion The full effect of the recent pesticide policy reform in Nepal remains to be seen. Our analysis shows a continuing increase in suicide numbers, despite bans of the most important pesticide in 2006. This may indicate smuggling across the border and the use of the brand name (Metacid) for pesticides in general making it difficult to identify the responsible pesticide. More information is required from forensic toxicology labs that identify the individual compounds found. The effect of recent bans of common suicide pesticides needs to be monitored over the coming years. Evidence from other Asian countries suggests that HHPs bans will lead to a marked reduction in suicides, as well as fewer cases of occupational poisoning.